Antibacterial Activity of Methanolic Exract of Basidiomycetes - Karthiga, K.; Sivakumar, T. (Asian Journal of Chemistry, 2010)
The antibacterial properties of Lentinus sp., Pleurotus aureovillosus and Schizophyllum commune were investigated against bacterial strains namely Pseudomonas aeruginosa, Salmonella abony, Bacillus cereus and Staphylococcus aureus. The methanolic extracts of these three mushrooms showed better antibacterial activity against S. aureus and B. cereus. In contrast, the antibacterial activity of P. aureovillosus was reported to be positive for the both Gram positive and Gram negative bacteria.